Towards ensuring reproducibility of outsourced data generation. - Daniel B Sloan; Mark D Stenglein (PLoS Biology)
"Big data" generated from outsourced or centralized facilities often lacks methodological information. Here, we outline how and why researchers, service providers, and other parties should report on methodology and sample metadata to improve scientific reproducibility.